PD-L1 and prognosis in patients with malignant pleural mesothelioma: a meta-analysis and bioinformatics study. (September 2020) - Jin, Liu; Gu, Weiling; Li, Xueqin; Xie, Liang; Wang, Linhong; Chen, Zhongwen
Background: The prognostic value of programmed death-ligand 1 (PD-L1) expression in patients with malignant pleural mesothelioma (MPM) has been controversial according to previous investigations. Therefore, we conducted a meta-analysis to assess the potential prognostic significance of PD-L1 expression in MPM. Methods: PubMed, Embase, Web of Science, Scopus, and the Cochrane Library were thoroughly searched for relevant original articles published before 9 April 2020. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) of overall survival (OS) and progression-free survival (PFS) were calculated. The results of the meta-analysis were verified using The Cancer Genome Atlas (TCGA) dataset. Results: In total 16 studies were included in our meta-analysis. A high PD-L1 expression was associated with a poor OS (HR = 1.53, 95% CI = 1.28–1.83, p < 0.001), but not a grave PFS (HR = 1.07, 95% CI = 0.82–1.39, p = 0.643) in MPM. Furthermore, the PD-L1 expression correlated with the sarcomatoid + biphasic type of MPM (odds ratio = 4.32, 95% CI = 2.16–8.64, p < 0.001). TCGA data indicated that PD-L1 was a significant prognostic factor for OS (HR = 2.069, 95% CI = 1.136–3.769, p = 0.0175), but not for PFS (HR = 1.205, 95% CI = 0.572–2.539, p = 0.624), which was in accordance with the results of the meta-analysis. Conclusion: A high PD-L1 expression is a significant prognostic factor for poor OS of patients with MPM. We therefore suggest that PD-L1 expression levels can be used to predict the clinical outcomes of patients with MPM in the future.